2010
DOI: 10.1021/jp104198p
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum Mechanical Study of Methacrylate Free-Radical Polymerizations

Abstract: Theoretical calculations at the semiempirical and ab initio levels of theory have been completed for a series of methacrylate compounds reported in the literature as measured by pulsed-laser initiated polymerization in conjunction with size-exclusion chromatography (PLP-SEC). Modeling includes calculation of the Gibb's free energies (ΔG(‡)) and activation energies (E(a)). These results were then compared to experimental results. Semiempirical ΔG(‡) using AM1-CI calculations successfully predicted relative acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The same work also examined solvent effects on the tacticity of MMA polymerization using explicit solvent molecules, as well as a polarizable dielectric continuum model, showing that alcohol solvents can restrain the formation of isotactic structures when there exists hydrogen bonding between solute and solvent molecules . Miller and Holder studied structure–activity relationships in the homopolymerization of methacrylates and found that the electronic effect of radicals could be responsible for large propagation rate coefficients of large methacrylate monomers . Yavuz and Çiftçioğlu benchmarked the performance of various functionals using density functional theory (DFT) in the complete basis set (CBS) limit on the first step of MA polymerization.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The same work also examined solvent effects on the tacticity of MMA polymerization using explicit solvent molecules, as well as a polarizable dielectric continuum model, showing that alcohol solvents can restrain the formation of isotactic structures when there exists hydrogen bonding between solute and solvent molecules . Miller and Holder studied structure–activity relationships in the homopolymerization of methacrylates and found that the electronic effect of radicals could be responsible for large propagation rate coefficients of large methacrylate monomers . Yavuz and Çiftçioğlu benchmarked the performance of various functionals using density functional theory (DFT) in the complete basis set (CBS) limit on the first step of MA polymerization.…”
Section: Introductionmentioning
confidence: 97%
“…However, some recipes for acrylate-based materials can contain multiple bulky monomers, , and cross-propagation rate coefficients, including a wide diversity of possible penultimate or higher order effects, are needed to quantitatively describe the system. , Therefore, it is desirable to have theoretical methods that can be used as a complement to experimental measurements to predict all possible rate coefficients accurately. Quantum chemistry calculations have been increasingly used as an alternative approach to support and to enrich experimental studies of polymeric reactions. They are able to provide kinetics information for each possible combination of monomers and penultimate effects to establish structure–reactivity relationships. ,, The calculated propagation rate coefficients can be used selectively for modeling polymerization processes to gather useful information about MWD and chain sequences. The structure–reactivity relationships can facilitate screening of monomers for the design of new polymers with targeted properties, and they can be extended to systems of monomers beyond those employed to develop the structure–reactivity relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons of the formation of alternate polymers by MA and olefins are still unclear in detail. The methods of quantum chemistry based on the density functional theory were successfully used for the analysis of different radical polymerization processes [50][51][52], including homo-and copolymerization of acrylates [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], acrylamides [70,72,73], and acrylonitrile [74]. However, as far as we know, DFT-based methods have not been extensively used for visualization and comprehensive analysis of the free radical alternating copolymerization of donor and cyclic acceptor monomers, except the publications of Matsumoto et al, devoted to the copolymerization of N-methylmaleimide (MMI) with olefins [75], and MA with 2,4-dimethylpenta-1,3-diene [76].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum mechanical methods represent a powerful tool for evaluating the details of the reaction mechanisms on the atomistic scale. Here, all the reaction mechanisms present in polymerization reactions can, in principle, be captured with high fidelity 16–19. However, these techniques, as powerful as they are, are limited in their ability to model polymerizations of long chain macromolecules mainly due to available computation resources.…”
Section: Computer Simulation Approaches For Polymerization In Bulkmentioning
confidence: 99%